Relative susceptibility of five strawberry cultivars to Meloidogyne hapla under three soil water deficit levels - Khanizadeh, S.; Bélair, G.; Lareau, M.J. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1994)
The relative susceptibility of five strawberry (Fragaria x ananassa Duch.) cultivars to the root-knot nematode (Meloidogyne hapla) was tested under three different soil water deficit levels and three nematode densities. 'Bounty' was the most susceptible cultivar and 'Glooscap' the least susceptible for parasitism by M. hapla. Percent water deficit had a positive linear effect on the number of galls on strawberry roots, and on egg production and number of M. hapla larvae in the soil, regardless of cultivar type. Different population densities of the nematode had no effect on the final number of strawberry flower clusters, stolons and crowns. The initial M. hapla population had a quadratic effect on the number of galls on strawberry roots and on the number of larvae in the soil, but had a positive linear effect on M. hapla egg production. The harmfulness of this species to strawberry total yield and fruit size is questionable and requires further investigation.